Animal Welfare Assessment in 16 Zoos in South Korea Using the Modified Animal Welfare Assessment Grid - Ma, Seung-Aee; Kang, Hye-Jin; Lee, Kyuyoung; Kim, Sun-A.; Han, Jin Soo (Frontiers in Veterinary Science, 2022)
Various assessment tools that have been proposed thus far have disadvantages in that they are complex, time-consuming, non-objective, and not convenient for assessing multiple zoos. This study aimed to develop a simple, objective, and reliable welfare assessment tool, the modified Animal Welfare Assessment Grid (AWAG), that can be applied in South Korea, where there is no licensing system for zoos. The AWAG has four main sections: physical, psychological, environmental, and procedural. These four sections include 23 welfare factors like general conditions, behaviors, housing, and restraints, for which each individual or group of animals is given a score. The modified AWAG system was applied by converting the 10-point rating scale of the original AWAG to a 6-point Likert scale. Sixteen zoos in Korea were selected based on the zoos with the most animals. Three inspectors assessed the scores of each animal and then averaged the results. The total data surveyed included 16,065 items. Zoos were largely classified into four grades based on the size of the zoo, animal species, and operating organization. In a relatively short period of 14 days, all the zoos were successfully assessed. Despite the shortened and modified assessment tool, the inter-rater reliability among inspectors was 0.942 with high objectivity. The modified AWAG could identify welfare differences between grades of Korean zoos. There were large differences between zoos in most environmental sections and some zoos were evaluated as having inadequate welfare levels. The modified AWAG showed high usability and objectivity. In addition, it was possible to determine which environmental or procedural sections could potentially help improve physical and psychological scores. The modified AWAG is an objective method that could set the direction for the improvement of zoo welfare in the future.